Total loss of GM3 synthase activity by a normally processed enzyme in a novel variant and in all ST3GAL5 variants reported to cause a distinct congenital disorder of glycosylation. (7th January 2019) - Indellicato, Rossella; Parini, Rossella; Domenighini, Ruben; Malagolini, Nadia; Iascone, Maria; Gasperini, Serena; Masera, Nicoletta; dall'Olio, Fabio; Trinchera, Marco
Abstract: ST3GAL5-CDG is a rare syndrome which is caused by variant GM3 synthases, the enzyme involved in the biosynthesis of a–b–c-series gangliosides. Here we report a novel homozygous ST3GAL5 variant, p.Gly342Ser, in a patient suffering from failure to thrive, severe hearing, visual, motor, and cognitive impairment, and respiratory chain dysfunction. A GM3 synthase assay towards the natural acceptor substrate lactosylceramide was performed upon transfection in HEK-293T cells of expression plasmids carrying wild type and mutated ST3GAL5 cDNAs. The assay revealed a complete loss of enzyme activity. Identical results were obtained with the other four ST3GAL5 variants which have been reported to be pathogenic. HEK-293T clones permanently expressing HaloTag-ST3GAL5 carrying each of the five variants were assessed by quantitative PCR, flow cytometry, western blotting and confocal microscopy. The results indicated that transcription, translation, stability and intracellular localization of the tagged protein were identical to those of the wild type construct. Compared with the very mild phenotype of st3gal5 KO mouse models, the results suggest that unknown mechanisms, in addition to the lack of a–b–c-series gangliosides, contribute to the syndrome. Direct enzyme assay upon transfection in model cells appears to be an effective tool for characterizing variants of glycosyltransferases involved in glycosphingolipid biosynthesis.